PENGARUH PEMBIAYAAN MUDHARABAH DAN MUSYAROKAH TERHADAP ROE PADA BANK BCA SYARIAH - Alifia Rizqi Nurul Aziza; Nana Diana (Prodi Ekonomi Syariah Universitas Majalengka, 2021)
The high level of ROE illustrates that the company's income is high so that management performance in managing the company is considered good. This research aims to analyze the Return On Equity (ROE) influenced or not by mudharabah financing and musyarakah financing at Bank BCA Syariah. Data is taken from financial reports at Bank BCA Syariah for the 2017-2019 period. Descriptive research using a quantitative approach includes this type of research. The analysis technique used consists of multiple regression analysis, descriptive statistical analysis, classical assumption test, and hypothesis testing. The results of the test state that mudharabah financing has no effect but is partially negative towards ROE. Musyarakah financing has a significant positive effect on Return On Equity partially.